2021
DOI: 10.1016/j.jseint.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Biological sex impacts perioperative complications after reverse shoulder arthroplasty for proximal humeral fracture

Abstract: Background The purpose of this study was to determine the difference in complication rates between males and females undergoing reverse shoulder arthroplasty for proximal humerus fractures. We hypothesized that (1) females were more likely to undergo reverse shoulder arthroplasty for fracture, and (2) males were more likely to sustain a perioperative complication. Methods The National Surgical Quality Improvement Program database was queried to identify patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“… 34 In addition, Ezuma et al documented men were 2.38 times more likely to have perioperative and postoperative RSA complications and 10.59 times more likely to return to the operating room for an unplanned reoperation than women even though significantly more women compared with men older than 65 years underwent RSA for proximal humerus fractures. 11 Male patients and patients with multiple comorbidities in the setting of a complex proximal humerus fracture may be at a higher risk of complications with RSA. In concert with previous literature, the present study reported men in the 65 years and older cohort to be significantly less likely to receive RSA for a proximal humerus fracture than similarly aged women.…”
Section: Discussionmentioning
confidence: 99%
“… 34 In addition, Ezuma et al documented men were 2.38 times more likely to have perioperative and postoperative RSA complications and 10.59 times more likely to return to the operating room for an unplanned reoperation than women even though significantly more women compared with men older than 65 years underwent RSA for proximal humerus fractures. 11 Male patients and patients with multiple comorbidities in the setting of a complex proximal humerus fracture may be at a higher risk of complications with RSA. In concert with previous literature, the present study reported men in the 65 years and older cohort to be significantly less likely to receive RSA for a proximal humerus fracture than similarly aged women.…”
Section: Discussionmentioning
confidence: 99%
“…This finding echoes that of Ezuma et al, who used the National Surgical Quality Improvement Program database to compare complication rates after RTSA for PHF and found that males had a 2.4-fold risk of developing any 30-day complication and a 10-fold risk of 30-day reoperation. 21 Male sex has also been shown to be an independent risk factor for instability and dislocation, 22 re-admission, 23 and reoperation after RTSA. 24 Between 2000 and 2017, the proportion of patients treated with hemiarthroplasty dropped from 31% to 12%.…”
Section: Discussionmentioning
confidence: 99%
“…After RTSA for proximal humeral fracture, however, sex-specific literature is scarce. A database analysis by Ezuma et al confirmed an increased risk for secondary surgery and any complication in male patients, although their cohort included only 175 men [ 48 ]. In a multicentre retrospective review of 898 patients, Gallinet et al reported a rate of 12.5% overall complications with a 5% revision rate, without a sub-analysis of patient sex [ 49 ].…”
Section: Discussionmentioning
confidence: 99%